Phakomatosis pigmentovascularis presenting with Sturge-Weber syndrome and Klippel-Trenaunay syndrome - Sumit Sen; Sanchaita Bala; Chinmay Halder; Rahul Ahar; Anusree Gangopadhyay (Wolters Kluwer Medknow Publications, 2015)
Phakomatosis pigmentovascularis (PPV) is a rare cutaneous disorder characterized by combination of capillary malformation and other pigmented naevi. Four types and two subtypes have been described where subtype 'a' present only with cutaneous form and subtype 'b' also with systemic association like in Sturge-Weber syndrome or Klippel-Trenaunay syndrome. Hereby, we report a case where our patient presented with port-wine stain, Nevus of Ota, Sturge-Weber syndrome, and Klippel-Trenaunay syndrome; which has made it a rare combination.